MONITORING OF SUSTAINABLE DEVELOPMENT OF THE INDUSTRY BASED ON A MULTI-CRITERIA APPROACH - Dmitriy N. Lapaev; Evgeniy S. Mityakov; Ekaterina S. Mokretsova (Статистика и экономика, 2016)
The article suggests the method of monitoring the sustainable development of the industry based on multi-criteria approach. This method involves a search of effective sets of industries based on predicted data. This technique is tested on thirteen branches of manufacturing industry in the article. The authors chose two systems of estimated indicators that characterize production stability and impact of social, environmental and technogenic threats.